2022
DOI: 10.3390/ma15093213
|View full text |Cite
|
Sign up to set email alerts
|

Structural Behavior of FRP-Retrofitted RC Beams under Combined Torsion and Bending

Abstract: Fiber-reinforced polymers (FRPs) retrofit reinforced concrete (RC) structures. ABAQUS finite element software was used to perform numerical parametric analysis on a group of RC beams in this research. All specimens were retrofitted by FRP strips as an external retrofitting and experimentally tested up to previous researchers’ failure points. The range of subjects examined in these RC beams included cracking torque, ultimate torque, angle of twist, and the effect of using FRP on these subjects. We applied artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Therefore, it is necessary to study the response of a single frame under load combinations. According to relevant studies [17,18], steel frame beams are mainly subjected to torsion and shear forces. In a finite element simulation, steel frame structures are subjected to dead loads, live loads, wind loads, and vertical and horizontal seismic loads.…”
Section: Load Conditions On the Framementioning
confidence: 99%
“…Therefore, it is necessary to study the response of a single frame under load combinations. According to relevant studies [17,18], steel frame beams are mainly subjected to torsion and shear forces. In a finite element simulation, steel frame structures are subjected to dead loads, live loads, wind loads, and vertical and horizontal seismic loads.…”
Section: Load Conditions On the Framementioning
confidence: 99%
“…Santhakumar et al presented numerical research on non-retrofitted and retrofitted RC beams exposed to combined bending and torsion utilizing the finite element method [8]. Ahad et al used ABAQUS to conduct finite element analysis for increasing the orientation of different FRP-reinforced and unreinforced concrete beams [9].…”
Section: Project Overviewmentioning
confidence: 99%
“…25 It was observed that the Finite Element (FE) models available in the ABAQUS platform give a reasonable prediction for the RC structural elements. 26 Theoretical analysis of the bending resistance of ECC-concrete composite beams was developed and compared well with the experimental results. 27,28 Analytical techniques and simplified formulas for the calculations of cracking, yield, and ultimate moments of different cases as well as deflections of ECC-concrete composite beams reinforced with steel bars were proposed.…”
Section: Introductionmentioning
confidence: 99%
“…For an accurate numerical prediction of the behavior of ECC elements, adequate material models, which can represent the behavior of ECC, are essential 25 . It was observed that the Finite Element (FE) models available in the ABAQUS platform give a reasonable prediction for the RC structural elements 26 …”
Section: Introductionmentioning
confidence: 99%